Чекисты Петрограда на страже революции - Кутузов В. А. Владимир Александрович; Лепетюхин В. Ф. Владимир Федорович; Седов В. Ф. Владимир Федорович; Степанов О. Н. Олег Николаевич (Ленинград, Лениздат, 1987)
Посвящается 70-й годовщине Великого Октября и 70-летию ВЧК-КГБ